(untitled) (Journal of Fiber Bioengineering and Informatics, 2019)
Polytetrafluoroethylene (PTFE) membrane is widely used in medicine, clothing, chemical, electronics and other fields. However, due to the highly symmetrical structure of the PTFE, the absence of reactive radical, high crystallinity, low surface energy and poor surface wetting, these properties of PTFE affect its compound with other materials. In order to improve the adhesion property of PTEF membrane, the surface must be modified. In this paper, the surface melting deposition method was used to improve the hydrophilicity of PTFE membrane. The PTFE membrane is immersed in a suspension of nano-TiO2, and then deposited by melting at a high temperature. Sintering and depositing TiO2 particles on the surface of the PTFE membrane. The molecules of the viscous substance enter the surface layer of the PTFE membrane to form a modified surface layer. The interface strength of PTFE membrane is increased, and the surface activity of PTEF membrane is increased, and the hydrophilicity of the PTFE membrane is improved. It is easier that PTFE membrane is combined with other materials. The best treatment process for the modification by melting deposition is as follows: the optimum treatment temperature is 350◦C, and the optimum treatment time is 30 min.